BUSINESS DEVELOPMENT CONSTRAINTS IN ROMANIA'S CENTER REGION ENTREPRENEURS' OPINIONS - Călina, BUŢIU Ana (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 20 (2018): Annales Universitatis Apulensis Series Oeconomica, 2018)
Taking into account the economic importance of business development in the region, a survey was undertaken to identify Center Region's business owners' perceptions of what constitutes barriers to growing their enterprise. To that purpose there were conducted both an analysis of the latest studies and reports on the issue and a qualitative survey of a selected lot of entrepreneurs from all six counties of the Center Region. The results support a series of conclusions with useful suggestions for the improvement of the entrepreneurial environment.